2016
DOI: 10.1080/00207543.2016.1191691
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for quality improvement efforts coordination in supply chains with partial cost allocation contract

Abstract: In this paper, we consider quality improvement efforts coordination in a two-stage decentralised supply chain with a partial cost allocation contract. The supply chain consists of one supplier and one manufacturer, both of which produce defective products. Two kinds of failure cost occur within the supply chain: internal and external. The supplier and the manufacturer determine their individual quality levels to maximise their own profits. We propose a partial cost allocation contract, under which the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 18 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…He suggested an integrated model to cut the production of substandard items. Gao [15] developed a probabilistic models for the production and operational incitements by improving quality and coordination in supply chains with cots allocations. Majumder et al [28] and Dey et al [13] proposed the improvement in the production quality with the reduction in setup cost and setup time for vendor-buyer supply chain model.…”
Section: Quality Deterioration During Production Processmentioning
confidence: 99%
“…He suggested an integrated model to cut the production of substandard items. Gao [15] developed a probabilistic models for the production and operational incitements by improving quality and coordination in supply chains with cots allocations. Majumder et al [28] and Dey et al [13] proposed the improvement in the production quality with the reduction in setup cost and setup time for vendor-buyer supply chain model.…”
Section: Quality Deterioration During Production Processmentioning
confidence: 99%
“…It is shown that increasing efficiency to get financial advantages is obviously more attractive. Profit is still the most important performance indicator in SCC research, although quality and environment are paid more and more attentions in recent years, such as Yang, Lu, and Xu (2016), Xiao, Yang, and Shen (2011) and Gao et al (2016) in the International Journal of Production Research. It is anticipated to have more similar SCC studies addressing the improvement of quality and environment-related performance in future research.…”
Section: Conclusion and Further Research Directionmentioning
confidence: 99%
“…This finding is unique in the literature on supply chain management. Furthermore, Gao et al [ 13 ] considered single and double moral hazard models with quality level uncertainties and proposed a partial cost allocation contract which can fairly allocate defective costs.…”
Section: Literature Reviewmentioning
confidence: 99%